2015
DOI: 10.1021/acs.organomet.5b00242
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Osmium Hydrido Alkenylcarbyne with Allenoates: Insertion and [3 + 2] Annulation

Abstract: Treatment of the osmium hydrido alkenylcarbyne complex [OsH{CC(PPh 3 )CHPh}(PPh 3 ) 2 Cl 2 ]BF 4 (1) with allenoates (CH 2 CCHCOOR, R = Me, Et) in the presence of excess AgBF 4 leads to the insertion products 2/3. The reactions of complex 1 with substituted allenoates, i.e., diethyl 2-vinylidenesuccinate (CH 2 CC(CH 2 COOEt)-(COOEt)) and ethyl penta-2,3-dienoate (CH(CH 3 )C CH(COOEt)), result in the formation of [3 + 2] annulation products 4 and 6, respectively. Mechanisms of the reactions have been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…However, the only tethered  6 -arene-osmium(II) described to date in the literature is the [3+2] annulation product of osmium hydrido alkenylcarbyne complex [OsH{CC(PPh 3 )CHPh}(PPh 3 ) 2 Cl 2 ] + with a substituted allenoate, which affords a typical three-legged piano-stool structure with the η 6 -benzene, two PPh 3 , and an alkenyl carbon atom (pendant from the arene) connected to the metal center. 47 In addition, octahedral complexes of formula [OsCl 2 (N^P) 2 ] have shown some cis versus trans fluxional conversion attributable to the hemilability of the N^P ligand in solution. 48 Organometallic Os(II) complexes have similar, often almost identical, structures to the analogous ruthenium compounds, yet they are often more inert, 49 a useful feature vis-à-vis exerting control over metal reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the only tethered  6 -arene-osmium(II) described to date in the literature is the [3+2] annulation product of osmium hydrido alkenylcarbyne complex [OsH{CC(PPh 3 )CHPh}(PPh 3 ) 2 Cl 2 ] + with a substituted allenoate, which affords a typical three-legged piano-stool structure with the η 6 -benzene, two PPh 3 , and an alkenyl carbon atom (pendant from the arene) connected to the metal center. 47 In addition, octahedral complexes of formula [OsCl 2 (N^P) 2 ] have shown some cis versus trans fluxional conversion attributable to the hemilability of the N^P ligand in solution. 48 Organometallic Os(II) complexes have similar, often almost identical, structures to the analogous ruthenium compounds, yet they are often more inert, 49 a useful feature vis-à-vis exerting control over metal reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, tethered osmium complexes are uncommon, and most of the examples currently known involve η 5 -cyclopentadienyl-type ligands connected to P- [9,10], N- [10], C- [11], or Sn-donor [12] groups. In fact, the only tethered η 6 -arene-osmium(II) derivatives described to date in the literature are compounds B, synthesized by Xia and co-workers from the reactions of the hydride-alkenylcarbyne complex A with allenoates (Scheme 2) [13]. All these facts prompted us to study the reactivity of the osmium(II) dimers [{OsCl(μ-Cl)(η 6 -arene)}2] (arene = p-cymene, benzene) towards phosphinites R2PO(CH2)nPh as a potential entry to tethered species related to those previously described for ruthenium.…”
Section: Of 10mentioning
confidence: 99%
“…31 P{ 1 H} NMR (121 MHz, CDCl 3 ): δ = 63.1 (s) ppm. 1 H NMR (300 MHz, CDCl 3 ): δ = 7.85-7.78 (m, 4H, Ph), 7.41-7.25 (m, 11H, Ph), 5.33 and 5.21 (d, 2H each, 3 J HH = 5.7 Hz, CH of p-cymene), 3.95 (td, 2H, 3 J HH = 6.3 Hz, 3 J PH = 5.1 Hz, OCH 2 ), 2.93 (t, 2H, 3 J HH = 6.3 Hz, CH 2 Ph), 2.40 (sept, 1H, 3 J HH = 6.9 Hz, CHMe 2 ), 1.87 (s, 3H, Me), 1.10 (d, 6H, 3 J HH = 6.9 Hz, CHMe 2 ) ppm 13. C{ 1 H} NMR (100 MHz, CDCl 3 ): δ = 138.7 (s, C ipso of Ph), 136.3 (d, 1 J PC = 56.2 Hz, C ipso of PPh), 132.5 (d, J PC = 9.7 Hz, CH ortho or CH meta of PPh), 130.7 (s, CH para of PPh), 129.3 and 128.4 (s, CH ortho and CH meta of Ph), 127.7 (d, J PC = 8.8 Hz, CH ortho or CH meta of PPh), 126.5 (s, CH para of Ph), 102.8 and 91.7 (s, C of p-cymene), 81.4 and 80.2 (s, CH of p-cymene), 67.6 (s, OCH 2 ), 37.1 (s, CH 2 Ph), 29.9 (s, CHMe 2 ), Molbank 2020, 2020, M1110 6 of 10 21.9 (s, CHMe 2 ), 17.1 (s, Me) ppm.…”
mentioning
confidence: 99%
“…Allene compounds can also adopt as unsaturated source to undergo analogous [4+2] cycloaddition reactions with metallaaromatics. As shown in Scheme , treatment of osmium hydrido alkenylcarbyne 36 with diethyl 2‐vinylidenesuccinate in the presence of excess AgBF 4 in dichloroethane at 60 °C for 2 days results in the osmium vinyl complex 38 . When the reaction was performed at room temperature or the reaction time was shorten to 1 h, two inseparable isomers, osmanaphthalene intermediates 37 and 37′ , were isolated as a red solid.…”
Section: Reactions With Unsaturated Compoundsmentioning
confidence: 99%
“…As shown in Scheme 18, treatment of osmium hydrido alkenylcarbyne 36 with diethyl 2-vinylidenesuccinate in the presenceo fe xcess AgBF 4 in dichloroethane at 60 8Cf or 2days results in the osmium vinyl complex 38. [35] When the reaction was performed at room temperatureo rt he reaction time was shorten to 1h,t wo inseparable isomers,o smanaphthalenei ntermediates 37 and 37',w erei solated as ar ed solid. Heating the mixture of 37 and 37' could furtherc onvert to the annulation product 38.T he experimental results indicated that the osmanaphthalenes 37 and 37' are the key intermediates of this conversion.…”
Section: [4+ +2] Cycloaddition Reactions With Alkynes or Allenesmentioning
confidence: 99%